Different responses involving Tfh cells delay parasite-specific antibody production in Trypanosoma cruzi acute experimental models - Leão, Ana Carolina; Villar, Maria Jose; Adhikari, Rakesh; Poveda, Cristina; Versteeg, Leroy; Almeida, Gregório; Hotez, Peter J.; Bottazzi, Maria Elena; Jones, Kathryn M. (Frontiers in Immunology, 2025)
IntroductionChagas disease (CD), caused by the parasite Trypanosoma cruzi, affects millions globally. Despite treatment options in the acute phase, most infections progress to a chronic indeterminate form or develop severe cardiac/gastrointestinal complications. Understanding the immune response is crucial for the development of vaccines and more efficient drugs for the disease control.MethodsThis work investigates the immune response to T. cruzi H1 K68 strain infection in female BALB/c and C57BL/6 mice to characterize differences in Tfh and B cell responses that may be involved in the poor parasite-specific antibody production during acute infection. For this, mice were euthanized 14, 28, and 49 days after infection, and splenic T and B cell populations were evaluated by flow cytometry.ResultsBALB/c mice exhibited a strong Th2-biased response with a massive expansion of classic Tfh cells and GC B cells, potentially linked with polyclonal B cell activation and hypergammaglobulinemia, but not with efficient parasite clearance. C57BL/6 mice displayed a Th1-skewed response with a population of "Th1-like Tfh" cells expressing IFN-γ and CXCR5 associated with lower parasite burden and more focused antibody response, including parasitespecific IgG2c during early acute infection.DiscussionThese findings suggest that these mouse models develop different immune responses mediated by Tfh cells, which are crucial for B cell activation and antibody production. The massive expansion of Tfh cells in BALB/c mice might lead to unspecific antibody production due to excessive B cell activation. Conversely, C57BL/6 mice exhibit a "Th1-like Tfh" response lacking classic Tfh cells, potentially explaining their weak parasite-specific antibody production throughout the acute infection. Overall, this study provides for the first time insights into the complex interplay between Tfh cells and antibody production during T. cruzi infection, suggesting potential targets for therapeutic intervention in CD.